Candidates' Papers (Hanscomb-Haward)
Date of appointment indicated in brackets after the name. Hanscomb, P. B. (1902) Hardie, J. M. (1939) Hardyman, A. V. (1916) Harley, W. (1937) Harlow, E. A. (1924) Harman, D. J. (1939) Harman, R. A. (1915) Harman, S. S. (1908) Harmon, F. H. B. (1929) Harries, Gladys M. (1909) Harries, T. O. (1912) Harrison, Florence (1927) Harrop, Marion K. (1937) Haward, J. Edith (1913) Haward, M. Ethel (1917)